2009
DOI: 10.1080/03057640903352465
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of disabled students in initial teacher education

Abstract: This paper reports on a survey that aimed to explore the experiences of students undertaking initial teacher education and community education degrees in a Scottish University. The survey focused in particular on decisions around disclosure of disability and experiences on 'placements' in schools or community work settings. Findings indicated that many students chose not to disclose their disability, and for those who did this was a very individual process that was made up of a series of negotiations, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Botham & Nicholson, 2014;Brown, James, & MacKenzie, 2006;Griffiths, 2012;MacLeod & Cebula, 2009;Riddell et al, 2007). In addition, the only research study, prior to the research presented in this paper, that has investigated the experience of disabled and non-disabled students on professional programmes, compared the degree outcomes of students on one initial teacher education (ITE) programme (Fuller, Healey, Hurst, Riddell & Wareham, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botham & Nicholson, 2014;Brown, James, & MacKenzie, 2006;Griffiths, 2012;MacLeod & Cebula, 2009;Riddell et al, 2007). In addition, the only research study, prior to the research presented in this paper, that has investigated the experience of disabled and non-disabled students on professional programmes, compared the degree outcomes of students on one initial teacher education (ITE) programme (Fuller, Healey, Hurst, Riddell & Wareham, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…White, 2007), the timing of disability disclosure (e.g. MacLeod & Cebula, 2009), and the availability of support (e.g. Morris & Turnbull, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The few discussions that have taken place relating to teacher diversity in terms of (dis)abilites have brought forth contradictions. For example, in the UK the necessity of teacher trainees' increased literacy and numeracy standards (Macleod & Cebula, 2009;Riddick & English, 2006) has led to questioning whether individuals with specific learning difficulties are suitable applicants for teaching positions (Singleton, 1999;O'Dwyer & Thorpe, 2013). A pool of studies illustrate that the number of students with specific learning difficulties entering higher education has increased (Griffin & Pollak, 2009;Griffiths, 2012;Kunttu & Pesonen, 2013;Valle, Solis, Volpitta, & Connor, 2004).The latest statistics reveal that 5% of students in Finnish HE have a learning difficulty of which dyslexia has been notified as the most common condition (74%) among them (Kunttu & Pesonen, 2013).…”
Section: Diversity Within the Teaching Workforcementioning
confidence: 99%
“…This has raised questions whether individuals with dyslexia are suitable applicants for teaching (Singleton, 1999;O'Dwyer & Thorpe, 2013) In contrast, research confirms that people with dyslexia have been found to be highly successful and effective at the highest occupational levels, including in the teaching profession (Logan, 2009;Reid, Came, & Price, 2008;West, 2010in Leather et al, 2011. Previous studies on the experiences of teacher trainees' from Canada, UK and US (Duquette, 2000;Glazzard & Dale, 2013;Griffiths, 2011;Macleod & Cebula, 2009;Morgan & Rooney, 1997;Riddell & Weedon, 2013;Riddick, 2003) as well as of those practicing teachers with dyslexia (Ferri, Connor, Solis, Valle & Volpitta, 2005;Ferri, Keefe & Gregg, 2001;O'Dwyer & Thorpe, 2013;Riddick, 2003;Valle et al, 2004;Vogel et al, 2007;Vogel & Sharoni, 2011) confirm their existence. How then do tertiary teachers with dyslexia perceive themselves as teachers and negotiate their professional identities?…”
Section: Adult Dyslexia In Teaching Contextmentioning
confidence: 99%
See 1 more Smart Citation